1994
DOI: 10.1128/aac.38.8.1854
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of antimalarial endoperoxides with specific parasite proteins

Abstract: The endoperoxides are a new class of antimalarial agents, ofwhich artemisinin (qinghaosu) is the prototype.We have previously shown that artemisinin is capable of alkylating proteins in model reactions. In the present study, we showed that when Plasmodium falciparum-infected erythrocytes are treated with a radiolabeled antimalarial endoperoxide, either arteether, dihydroartemisinin, or Ro 42-1611 (arteflene), the radioactivity is largely coverted into a form which can be extracted with sodium dodecyl sulfate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
154
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(168 citation statements)
references
References 27 publications
10
154
0
4
Order By: Relevance
“…The IC 50 values for probe 1 (P1) and probe 2 (P2) were 43.86 (SD = 0.441 nM; n = 3) and 30.26 nM (SD = 0.314 nM; n = 3), respectively, compared with the IC 50 of ART of 14 nM (SD = 0.41 nM; n = 3). Importantly, control probes CP1 and CP2 were inactive in agreement with expectations (12,14). This result supports the essentiality of the endoperoxide bridge and validates our probe plus control pair strategy.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The IC 50 values for probe 1 (P1) and probe 2 (P2) were 43.86 (SD = 0.441 nM; n = 3) and 30.26 nM (SD = 0.314 nM; n = 3), respectively, compared with the IC 50 of ART of 14 nM (SD = 0.41 nM; n = 3). Importantly, control probes CP1 and CP2 were inactive in agreement with expectations (12,14). This result supports the essentiality of the endoperoxide bridge and validates our probe plus control pair strategy.…”
Section: Resultssupporting
confidence: 75%
“…We varied click handles to expand the utility of ART-ABPPs and compare the efficiency of two distinctive tagging chemistries (i.e., copper-catalyzed and bioorthogonal copper-free click chemistry). Previous work by Meshnick and coworkers (12) showed that six uncharacterized malaria proteins bands were labeled with semisynthetic derivatives of ART (e.g., [3H]-dihydroartemisinin) at pharmacologically relevant concentrations of the drug. Importantly, labeling was not shown using uninfected erythrocytes or when infected cells were treated with the inactive analog, deoxyether (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haem (130.2 mg, 0.125 mmol) and artemisinin (226.3 mg, 0.5 mmol) were dissolved in 1.6 ml of DMA and incubated with stirring at 37 • C for 24 h. The reaction mixture was then subjected to reverse-phase chromatography on a glass column with 20 g of C 18 resin pre-equilibrated with 30 % (v/v) acetonitrile/0.1 % trifluoroacetic acid. Chromatographic elution was done by using step gradients in the range 30-100 % (v/v) acetonitrile.…”
Section: Reaction Between Free Haem and Artemisininmentioning
confidence: 99%
“…The infected red blood cells, with extensive modifications in the plasma membrane, facilitate the active uptake of artemisinin into the food vacuole, creating a nanmolar to micromolar concentration gradient across the food vacuole membrane [16,17]. Several studies have suggested that the haem-promoted cleavage of the peroxide in artemisinin, leading to the formation of C-radicals which alkylate some proteins of the malaria parasite [18], also contributes to its antimalarial action. Specific reactions of artemisinin with TCTP (translationally controlled tumour protein) [19], inhibition of the SERCA (sarcoplasmic/endoplasmic-reticulum Ca 2+ -ATPase) orthologue (PfATP6) of P. falciparum [20] and inhibition of P. falciparum cysteine proteases have also been proposed to contribute to its drug activity [21].…”
Section: Introductionmentioning
confidence: 99%